The Impact of Gender and Class on Disease and Trauma in 18th Century London: A Case Study of Three Cemetery Populations - (:unkn) unknown (My University, 2020)
The bioarchaeological study of paleopathology integrates interdisciplinary approaches, such as gender and class theory, and the study of trauma and disease. Using multiple lines of evidence, this thesis examines the impact of gender and class on skeletal evidence for disease and trauma in three 18th century London cemeteries serving different socio-economic populations. Contemporary written sources for prescribed gender and class roles are tested against the bioarchaeological evidence to investigate the extent to which these norms reflected lived reality or differentially impacted the incidence of trauma and disease in populations of varying socioeconomic status. Conformity to prescribed gender roles should be reflected in higher rates of occupational trauma and disease in men because they were expected to engage in higher risk activities as the “protectors” of their families and households. Women, as the caretakers of children and the home, should exhibit lower rates of occupational trauma but higher rates of nutritional stress due to pregnancy, menopause and more limited access to nutrient-rich foods. Differential resource accessibility limiting rigid conformity to social norms predicts more fluid gender roles should be seen in lower class populations whereas class privilege permitting greater access to resources should be reflected in greater conformity to strict gender roles.
Keywords: 18th century; Bioarchaeology; Gender performance; London; Paleopathology